A Simple and Efficient Extraction Method for the Preconcentration of Copper in Tap Water and Linden Tea Samples Prior to FAAS Measurement. Issue 12 (26th March 2021) - Demir, Cansu; Öner, Miray; Bodur, Süleyman; Er, Elif Öztürk; Bakırdere, Sezgin
Abstract: In this study, a simple, low‐cost and eco‐friendly analytical method namely syringe assisted pipette tip dispersive solid phase extraction (SA‐PT‐DSPE) combined with slotted quartz tube‐flame atomic absorption spectrometry (SQT‐FAAS) system was presented for the determination of copper at trace levels in linden tea and tap water samples. Under the optimal experimental conditions, limit of detection (LOD) and quantification (LOQ) values obtained for the SA‐PT‐DSPE‐SQT‐FAAS system were calculated as 3.7 and 12.5 μg/L, respectively. The SA‐PT‐DSPE‐SQT‐FAAS system provided a 44.0‐folds improvement in detection power of the conventional FAAS. The recovery results for tap water samples were calculated close to 100 % via external calibration strategy. Negative matrix effects on the analyte were observed for linden tea samples. Therefore, recovery studies were performed by matrix matching calibration strategy and percentage recoveries were found to be between 88.0–102.0 % with low standard deviation values. Abstract : Syringe assisted pipette tip dispersive solid phase extraction (SA‐PT‐DSPE) method was developed to preconcentrate and extract copper prior to slotted quartz tube‐flame atomic absorption spectrometry (SQT‐FAAS) on the purpose of trace level detection/quantification of the analyte. Stearic acid coated Fe3 O4 nanoparticles were used as adsorbent for the preconcentration of analyte. A syringe system was used to enhance the interactions between analyte and nanoparticles.